Keperawatan Spiritual di Bali - Kadek Yudi Aryawan; Ni Kadek Diah Purnamayanti (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the description of spiritual nursing in Bali. The research method used is quantitative observational research with a cross-sectional approach. The research results on the fulfillment of spiritual needs by nurses in Bali are primarily in the medium category of 50%. At the same time, 32.5% are in the high class. Only 17.5% are in a common type. The fulfillment of spiritual needs by nurses in Bali is mainly in the medium and high categories. Only a tiny proportion of spiritual realization is in a low type. Caring has been embedded in nursing care, which is a form of implementing the spiritual dimension. In conclusion, the nurse's activity in implementing the concept of caring is an indirect part of spiritual care. A holistic and humanist approach is a strategy that needs to be instilled as part of professional nursing care. The aspect of spirituality is an essential dimension for providing excellent care in the era of disruption. Keywords: Tourism Health, Spiritual Nursing